Iron Age Hillforts and Defended Enclosures in Southwest Wales - K. Murphy; F. Murphy (Internet Archaeology, 2010)
Iron Age settlement in Wales is dominated by defended settlements, ranging in size from large multivallate hillforts to small farmsteads protected by a simple bank and ditch. There are a total of 787 defended settlements in southwest Wales (Carmarthenshire, Ceredigion and Pembrokeshire) alone, which include 59 definite or possible hillforts, 166 definite or possible promontory forts and 562 definite or possible defended enclosures. This short article summarises the results of several years' survey, during which all those defended settlement sites that had no statutory protection as Scheduled Ancient Monuments were visited and recorded, and one in ten scheduled sites were visited. A list of all sites, including those that are Scheduled Ancient Monuments, is presented in an appendix. It is not possible in such a short article to provide a complete analysis and synthesis of Iron Age settlement in southwest Wales, but the results of the survey are presented in as concise a form as possible, using tables and distribution maps accompanied by a short commentary and some contextual information.